Chestnut tannin induces gut degeneration in Aedes albopictus mosquito larvae - Linda Abenaim; Priscilla Farina; Angela Rosa Cuzzola; Loretta Guidi; Romano Dallai; David Mercati; Erika Carla Pierattini; Barbara Conti; Alessandro Mandoli (Environmental Science and Pollution Research, 2026)

Novel enzymatic cocktail enhances bioplastic hydrolysis and biomethane production during anaerobic digestion of organic fraction of municipal solid waste - Daniele Vezzini; Leonardo Faggian; Marthinus W. Myburgh; Lara Facchini; Angela Conti; Alessandra Lorenzetti; Marinda Viljoen-Bloom; Lorenzo Favaro (Bioresource Technology, 2026)

VEGF and the VEGF73-101 Fragment Prevent MPP+ Induced Mitochondrial Dysfunction in a Cell Model of Parkinson’s Disease - Stefania Zimbone; Giuseppe Battiato; Stefano Conti Nibali; Irina Naletova; Noemi Anna Pesce; Vito De Pinto; Angela Messina; Andrea Magrì; Marianna Flora Tomasello; Giulia Grasso (Molecular Neurobiology, 2025)
Vascular endothelial growth factor (VEGF) is best known for its role in angiogenesis, but emerging evidence suggests neurotrophic and neuroprotective functions most likely connected to energy homeostasis pathways. Using high-resolution respirometry, we investigated the role of VEGF in optimizing mitochondrial oxidative phosphorylation efficiency in neuronal-like cells. Our findings indicate that VEGF enhances coupling efficiency for ATP synthesis by reducing the uncoupled respiration, a process involved in mitochondrial dysfunction and neurodegeneration, as observed in Parkinson’s disease (PD). To investigate the VEGF relevance in PD, we exposed differentiated SH-SY5Y cells to MPP + , a toxin inducing a PD-like phenotype. Both VEGF and a mimic peptide (VEGF 73-101 ) reduced MPP + -induced uncoupled respiration, mitochondrial membrane potential (Δψm) collapse, and cell death. These effects were associated with Erk signaling activation, upregulation of PGC-1α genes expression and increased mitochondrial DNA. Our study underscores VEGF’s multifaceted role in neuronal resilience beyond angiogenesis. Furthermore, these findings suggest that the VEGF 73-101 fragment may retain key neuroprotective and neurotrophic properties supporting further exploration of its therapeutic potential.

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Plant Growth-Promoting Yeasts (PGPYs) as a sustainable solution to mitigate salt-induced stress on zucchini plant growth - Chiara Ruspi; Debora Casagrande Pierantoni; Angela Conti; Roberto Scarponi; Laura Corte; Gianluigi Cardinali (Biology and Fertility of Soils, 2025)

Spinal delivery of an AAV-vector stably expressing the VDAC1 mitochondrial protein restores cellular respiration in an ALS model mouse - Andrea Magrì; Cristiana Lipari; Giuseppe Battiato; Pietro Caruso; Iolanda Infantino; Stefano Conti Nibali; Angela Messina (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

New VDAC1-antagonist molecules promote patients’-derived cancer organoid death through mitochondrial-dependent metabolic interference - Stefano Conti-Nibali; Silvia De Siervi; Andrea Magrì; Christian Turato; Marco Lolicato; Angela Messina; Vito De Pinto (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Characterizing the role of cysteine residues in the biogenesis and maturation of VDAC3 - Giuseppe Battiato; Doron Rapaport; Stefano Conti Nibali; Simona Reina; Angela Messina; Vito De Pinto (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Soil microbiota resilience in a two-decade long-term experiment comparing an organic and a conventional cropping system - Debora Casagrande Pierantoni; Angela Conti; Laura Corte; Paolo Benincasa; Gianluigi Cardinali; Marcello Guiducci (Applied Soil Ecology, 2024)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Grey matter volume in developmental speech and language disorder - Lauren Pigdon; Catherine Willmott; Sheena Reilly; Gina Conti-Ramsden; Christian Gaser; Alan Connelly; Angela T. Morgan (Brain Structure and Function, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)